Academic bodies, resources and forced collegiality - Silva Montes, Cesar; Castro Valles, Alberto (Education Policy Analysis Archives, 2014)
In this paper the effects of the Faculty Improvement Program (Promep) of the academic staff of the Autonomous University of Ciudad Juarez (UACJ) are analyzed. Designed as a national policy to promote efficiency of university activities, to its promoters the professionalization of teachers and the development of academic groups (CA) improved the quality of teaching and scientific productivity. From the qualitative and ethnographic perspective, it was found that for the faculty of UACJ, this policy strengthened individualism, meritocracy and bureaucracy that hinders voluntary assessment, collegiality and intellectual engagement. So far, attempts to standardize management practices promoting academic obtaining recognition "Pomep desirable profile" and the consolidation of the CA, as a way to increase the financial resources allocated to the institution.